2019 28th IEEE International Conference on Robot and Human Interactive Communication (RO-MAN) 2019
DOI: 10.1109/ro-man46459.2019.8956386
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Human-Robot Trust through Music-Driven Robotic Emotion Prosody and Gesture

Abstract: As human-robot collaboration opportunities continue to expand, trust becomes ever more important for full engagement and utilization of robots. Affective trust, built on emotional relationship and interpersonal bonds is particularly critical as it is more resilient to mistakes and increases the willingness to collaborate. In this paper we present a novel model built on music-driven emotional prosody and gestures that encourages the perception of a robotic identity, designed to avoid uncanny valley. Symbolic mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Presentation includes the way the robot appears, such as changes based on different behavior ( Goetz et al, 2003 ). The final category, vocalics, includes concepts such as prosody ( Crumpton and Bethel, 2016 ), which have shown to improve trust and other human-robot interaction metrics ( Savery et al, 2019a ). The vast majority of these communication techniques require significant technical and financial expense and variation to a system, such as adding augmented reality technology or changing robot movements ( Saunderson and Nejat, 2019 ).…”
Section: Related Workmentioning
confidence: 99%
“…Presentation includes the way the robot appears, such as changes based on different behavior ( Goetz et al, 2003 ). The final category, vocalics, includes concepts such as prosody ( Crumpton and Bethel, 2016 ), which have shown to improve trust and other human-robot interaction metrics ( Savery et al, 2019a ). The vast majority of these communication techniques require significant technical and financial expense and variation to a system, such as adding augmented reality technology or changing robot movements ( Saunderson and Nejat, 2019 ).…”
Section: Related Workmentioning
confidence: 99%
“…The authors considered the robot's role in its environment and adjusted its form and personality to meet human needs. Another meta-study of trust in HRI showed that the attributes of a robot have more influence on trust than environmental and human-related factors [49].…”
Section: The Methodological Gapmentioning
confidence: 99%
“…From these studies, there are two works that present proposals for systems for automatic emotion detection (González & McMullen, 2020;Vinayagasundaram et al, 2016). Three other studies use techniques for generating affective or personalized music (Savery et al, 2019;Y.-C. Wu & Chen, 2016;Chen et al, 2020).…”
Section: Musical Composition Recommendation and Customizationmentioning
confidence: 99%